Fibroblast Growth Factor Receptor 4 Deficiency Mediates Airway Inflammation in the Adult Healthy Lung? - Easter, Molly; Garth, Jaleesa; Harris, Elex S.; Shei, Ren-Jay; Helton, Eric S.; Wei, Yuhua; Denson, Rebecca; Zaharias, Rennan; Rowe, Steven M.; Geraghty, Patrick; Faul, Christian; Barnes, Jarrod W.; et al. (Frontiers in Medicine, 2020)
Fibroblast growth factor receptor (FGFR) 4 has been shown to mediate pro-inflammatory signaling in the liver and airway epithelium in chronic obstructive pulmonary disease (COPD). In past reports, global FGFR4 knockout (Fgfr4-/-) mice did not show any lung phenotype developmentally or at birth, unless FGFR3 deficiency was present simultaneously. Therefore, we wanted to know whether the loss of FGFR4 had any effect on the adult murine lung. Our results indicate that adult Fgfr4-/- mice demonstrate a lung phenotype consisting of widened airway spaces, increased airway inflammation, bronchial obstruction and right ventricular hypertrophy consistent with an advanced COPD phenotype. Despite downregulation of FGF23 serum levels, IL-1 and IL-6 in the Fgfr4-/- lung and abrogation of p38 signaling, primary murine Fgfr4-/- airway cells showed increased expression of IL-1beta and TGF-beta as well as augmented secretion of IL-6, which correlated with decreased airway surface liquid depth as assessed by microOCT. These findings were paralleled by increased ERK phosphorylation in Fgfr4-/- airway cells when compared to their control wild type cells. Analysis of a murine model with constitutive activation of FGFR4 showed an attenuation of pro-inflammatory mediators in both lung and airway epithelium. In conclusion, we are the first to show an inflammatory and obstructive airway phenotype in the adult murine Fgfr4-/- lung, which might be due to upregulation of ERK phosphorylation in the Fgfr4-/- airway epithelium. Therefore, the adult global Fgfr4-/- mouse could potentially be used in the future as a novel severe COPD model.